Utilisation of Personal Care Services in Scotland: the Influence of Unpaid Carers - Lemmon, Elizabeth (International Journal of Population Data Science, 2019)
Scotland is unique in its collection of routine data for all individuals in receipt of social care services. This care encompasses home and personal care services, down to telecare and meals services. As the Scottish population continues to age and local authorities stretch shrinking budgets over an increasing number of people, there is a pressing need to understand how older people use these services to ensure they are delivered in an efficient and effective way. The availability of administrative data in Scotland provides an opportunity to explore how it might be used in a research setting to enhance this understanding. One area of interest concerns the relationship between unpaid care and formal care services. In particular, how unpaid carers might influence older peoples use of formal care services. Whether this influence is positive or negative will have important implications for the costs of care provision. The existing evidence on the impact of unpaid care on social care utilisation is extremely mixed. Scotland provides an interesting context in which to study this relationship because unlike many other jurisdictions, personal care in Scotland is provided free to all individuals aged 65+ who are assessed as needing it. This may affect the incentives faced by unpaid carers, leading to different conclusions about the relationship between unpaid and paid care, compared to previous literature. This paper uses Scotland's unique administrative Social Care Survey (SCS) for the years 2014-2016 to investigate how the presence of an unpaid carer influences personal care use by those aged 65+ in Scotland. The results suggest that unpaid care complements personal care services. Complementarity between unpaid and paid care may imply that incentivising unpaid care could increase personal care costs, and at the same time it points to the potential for unmet need of those who do not have an unpaid carer. The paper highlights some of the limitations of the administrative SCS but also demonstrates how it can be used in an effective way to enhance our understanding in an important, policy relevant area.